Linguistic and psychodidactic foundations of foreign language learning in the senior age group - Kic-Drgas, Joanna (Glottodidactica, 2010)
The article is an introduction to the discussion about the linguistic and psychodidactic concepts justifying the thesis that the senior language learners are able to learn foreign languages and that they can achieve educational success in the process of foreign language learning.